Clarifying concepts: “Well-being” in sport - Trainor, Lisa Raquel; Bundon, Andrea (Frontiers in Sports and Active Living, 2023)
The purpose of this commentary is to critique the application of well-being in the field of sport and exercise psychology and to provide recommendations for future research. Over the last decade well-being has been an increasingly popular concept under investigation. In the field of sport and exercise psychology, numerous scholars have examined and conducted research on well-being of athletes. While this research has resulted in an abundance of findings, there is concern in how the concept of well-being was applied, defined, and measured. The construct of well-being can be traced back to two distinct perspectives, hedonic well-being and eudaimonic well-being. These perspectives of well-being are based on different philosophical assumptions, and while they are compatible, they are theoretically distinct. In sport and exercise psychology, well-being has lacked consistent operationalization and measurement (i.e., theoretical alignment, single dimensions of hedonic or eudaimonic measured to make claims about the broader well-being constructs), is vague and loosely defined, and is often studied in isolation from a well-being perspective (i.e., no theoretical foundation). We conclude by offering three recommendations to move the field of well-being in sport research forward.